(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In offices related to software, working professors in schools, colleges, etc, people sit for longer hours. Due to this they suffer with many health issues like overweight, joint pain, back pain, etc. this has become an increasing problem now a days. To overcome this, the project is designed which is called as “intelligent office chair”. This chair instructs the person sitting on the chair if he/she sit for long duration. Also, this chair reminds the person to drink water or medicine in time and. To prove the concept practically, a proto type module is designed and developed using Arduino. IR sensor is also used to instruct the person, if he/she isn’t sitting properly. In addition, a voice chip is also interfaced to the Arduino controller that gives voice announcements to drink water, medicine, etc. We present the implementation of an IoT (Internet of Things) based intelligent chair that combines an embedded system and android device.